2019
DOI: 10.2196/14217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Acute Flaccid Paralysis Surveillance System in Polio-Free Jordan, 2012-2016: Retrospective Secondary Analysis

Abstract: BackgroundAs part of the polio-eradication strategy, the World Health Organization (WHO) has established a global acute flaccid paralysis (AFP) surveillance system. AFP surveillance has successfully helped Jordan achieve polio-free certification. However, there is a substantial risk of polio importation from neighboring countries including Syria and Iraq.ObjectiveThis study aimed to evaluate the AFP surveillance in Jordan and identify areas that need improvement.MethodsThis retrospective study is a secondary a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The gold standard of polio surveillance is testing stools from patients with acute flaccid paralysis (AFP) for poliovirus. The AFP surveillance is used to achieve or confirm polio-free status in many countries [28][29][30][31][32]. However, polio-free countries are challenged by the sensitivity criteria (at least one AFP case per 100000 children under the age of 15 years per year) [33].…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard of polio surveillance is testing stools from patients with acute flaccid paralysis (AFP) for poliovirus. The AFP surveillance is used to achieve or confirm polio-free status in many countries [28][29][30][31][32]. However, polio-free countries are challenged by the sensitivity criteria (at least one AFP case per 100000 children under the age of 15 years per year) [33].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that 83.2% of AFP cases received at least 3 doses of OPV/IPV vaccine, 13.8% received less than three doses (out of which 26.4% were not vaccinated at all), and the remaining cases were unspecified (3.0%). This vaccination rate of 83.2% is considered significantly high compared to the same rate in Congo (58.9%) between 2008 and 2014 21 , but relatively low compared to the 98.3% found in Ikwa Ibom state, Nigeria 7 .…”
Section: Vaccination Ratementioning
confidence: 56%
“…These numbers showed to be similar to the results recorded in a study conducted in Italy between 1997 and 2007 20 . However, similar studies in Jordan, Iran, Congo, and Bangladesh [21][22][23][24] suggested that the incidence was significantly higher in children under five years old.…”
Section: Afp Distribution By Age Groupsmentioning
confidence: 95%
“…In 76 percent of the cases, more than three doses of the vaccination were administered. 25,26 Furthermore, as part of the vaccine program, vaccination records are well protected at the provincial level. These data support and sustain the high level of poliovirus vaccine coverage in children under the age of one year.…”
Section: Resultsmentioning
confidence: 99%